The particularities of the development of creativity among library institution staﬀ (Confluenţe Bibliologice, 2026)
This article examines the concept of creativity, highlighting the forms of development and the intellectual factors that shape it. Creativity can serve as a means of professional and personal improvement for librarians, as well as a tool for integrating into society. In order for activities aimed at stimulating creativity to lead to performance, the article identifies creativity blockages and methods for enhancing creative potential.
Keywords: professional training; creativity; development of creative potential